1999
DOI: 10.1146/annurev.pharmtox.39.1.295
|View full text |Cite
|
Sign up to set email alerts
|

Cyclins and Cell Cycle Checkpoints

Abstract: The eucaryotic cell cycle is regulated by the periodic synthesis and destruction of cyclins that associate with and activate cyclin-dependent kinases. Cyclin-dependent kinase inhibitors, such as p21 and p16, also play important roles in cell cycle control by coordinating internal and external signals and impeding proliferation at several key checkpoints. Understanding how these proteins interact to regulate the cell cycle has become increasingly important to researchers and clinicians with the discovery that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
471
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 616 publications
(489 citation statements)
references
References 110 publications
(110 reference statements)
16
471
0
2
Order By: Relevance
“…p15, but not p16, is activated in response to transforming growth factor (TGF-β1) (Robson et al, 1999). However, p16 is regulated by a feedback loop with Rb (Johnson and Walker, 1999). Silencing of p15 gene can provide a selective advantage for tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…p15, but not p16, is activated in response to transforming growth factor (TGF-β1) (Robson et al, 1999). However, p16 is regulated by a feedback loop with Rb (Johnson and Walker, 1999). Silencing of p15 gene can provide a selective advantage for tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since PCB-induced cell proliferation was inhibited in p50 −/− mice, we hypothesized that the expression of cell cycle genes would be altered. The cell cycle control system is regulated by the activity of cyclins, cyclin-dependent kinases (CDKs) and cyclin-dependent kinase inhibitors (CKIs) (Johnson and Walker 1999). The mRNA levels of cyclins A2, B1, B2, C, D1 and D2 in liver were measured using RNase protection assays (RPAs).…”
Section: Nf-κbmentioning
confidence: 99%
“…These proteins form active complexes that trigger the transition from G1 to S phase of the cell cycle, which involves cyclin E/A and CDK2 (Johnson and Walker, 1999;MacLellan and Schneider, 1999;Sherr and Roberts, 1999). When we examined levels of these cell cycle proteins, we found dramatic decreases in cyclin D3, CDK6, and p27 KIP1 in the hearts and cardiomyocytes treated with ROCK inhibitor.…”
Section: Figmentioning
confidence: 99%
“…Besides inhibiting CDK activity, they facilitate the formation of an active cyclin D/CDK complex (Koff and Polyak, 1995;Johnson and Walker, 1999;Sherr and Roberts, 1999;Dotto, 2000;Sgambato et al, 2000). It has been shown that inhibition of ROCK activity by Y27632 increases p27 KIP1 protein levels in rat hepatic stellate cells (Iwamoto et al, 2000).…”
Section: Figmentioning
confidence: 99%